“By Virtue of Righteous Women Was Israel Redeemed:” The Support Institution of the Yishuv by Qupat Qiryat Ḥanna in the Mid-19th Century - Atia, Ronel (Women in Judaism, 2024)
The early Zionist revival movement and the renewed Jewish settlement in the Land of Israel from the beginning of the nineteenth century gained a diverse research interest. Such studies often give the impression that the immediate environment promoting these trends was led exclusively by male leadership. However, it seems that the place of women is almost absent in everything related to the movement, and their promotion is almost wholly. It is possible to exempt reference to this due to the social norms that generally prevailed regarding the function and role of women in Jewish spaces within various communities. Thus, the Jerusalem congregation established a donation fund for the Jewish community in Jerusalem. They imposed on women a fixed tax obligation corresponding to Jewish women's rituals such as Challah, Nida, and candle lighting. Since these dates associated with the lives of Jewish women occurred every week or every month, the sums collected in the funds were fairly substantial. Evidently, they were a significant source of income for Gabayim (treasurers) and Shadarim (emissaries), who originated from Eretz Israel. In this article, the historical background of the fund's establishment, including the use of the funds collected from it, is described.